Promising approaches of computer-supported dietary assessment and management—Current research status and available applications. Issue 12 (December 2015) - Arens-Volland, Andreas G.; Spassova, Lübomira; Bohn, Torsten
Highlights: Potential of scientific and applied tools for dietary management is highlighted. Different tools predominate research vs. commercial applications. Personal health records (PHR) or health care workflows are underutilised. Development of comprehensive databases and simpler user interfaces for data entry can enhance future use. Abstract: Purpose: The aim of this review was to analyze computer-based tools for dietary management (including web-based and mobile devices) from both scientific and applied perspectives, presenting advantages and disadvantages as well as the state of validation. Methods: For this cross-sectional analysis, scientific results from 41 articles retrieved via a medline search as well as 29 applications from online markets were identified and analyzed. Results: Results show that many approaches computerize well-established existing nutritional concepts for dietary assessment, e.g., food frequency questionnaires (FFQ) or dietary recalls (DR). Both food records and barcode scanning are less prominent in research but are frequently offered by commercial applications. Integration with a personal health record (PHR) or a health care workflow is suggested in the literature but is rarely found in mobile applications. Conclusions: It is expected that employing food records for dietary assessment in research settings will be increasingly used when simpler interfaces, e.g., barcode scanning techniques, and comprehensive food databases are applied, which can also support user adherence to dietary interventions and follow-up phases of nutritional studies.